The Diencephalic Syndrome of Russell: A Case Report - Roka, Yam B; Paudel, G; Bidur, KC; Munakomi, S (Journal of Nepal Paediatric Society, 2009)
Diencephalic Syndrome (DS) is also known as Russells Syndrome. This is associated with marked emaciation, locomotor hyperactivity, vomiting, and absence of obvious neurological signs and loss of subcutaneous fat. A 15-month old child who presented with hyperactivity, loss of weight and failure to thrive since bi rth is reported. On Computed Tomography he had a large supra sellar mass with extension into the third ventricle causing gross hydrocephalus. He underwent biventricular shunting followed by microscopic near total excision of the tumor. The histopathology revealed it to be fibrillary meningioma. Although DS is uncommon it must be kept as a differential diagnosis in all children who fail to grow despite adequate intake. Key words: Childhood tumors, glioma, hydrocephalus, russells syndrome, suprasellar mass DOI: 10.3126/jnps.v30i1.2464 Journal of Nepal Paediatric Society Vol.30(1) 2010 60-63